LikeWant: A new methodology to measure implicit wanting for flavors and fragrances. (March 2020) - Cereghetti, Donato; Chillà, Chiara; Porcherot, Christelle; Sander, David; Cayeux, Isabelle; Delplanque, Sylvain
Highlights: LikeWant measures consumers' effort mobilization to obtain flavors and fragrances as rewards. LikeWant measures wanting for a pleasant odor with odorless air as control. LikeWant discriminates between two fine fragrances from their rewarding properties. Force indicators are more sensitive than squeeze frequency. Implicit wanting analyzed as participants' irrational effort. Abstract: According to the incentive salience hypothesis framework (Berridge, 2007, 2012; Berridge & Robinson, 1998, 2003; Berridge, Robinson, & Aldridge, 2009), wanting and liking can be dissociated, suggesting that two products having similar liking levels could trigger different wanting behaviors in consumers. Defined as a motivational state that promotes approach toward and consumption of rewarding stimuli, wanting can be measured through the Pavlovian instrumental transfer (PIT) procedure. Having emerged from animal models, the PIT procedure aims to measure the effort exerted by an organism (consumer) to obtain a particular reward (product). By adapting and optimizing existing human PIT procedures, we developed LikeWant, an innovative behavioral method that measures consumers' motivation to pursue flavors and fragrances as rewards. Two studies were conducted to test the sensitivity of the LikeWant procedure. In the first experiment, we investigated the sensitivity of the LikeWant procedure to measure wanting for a pleasant odor with odorless air as a neutral control. In the second experiment, we assessed the ability of the LikeWant procedure to simultaneously measure wanting for two competing fine fragrances. The results showed that the LikeWant procedure is able to (1) measure wanting for a pleasant odor with odorless air as a neutral control condition and (2) discriminate between two fine fragrances on the basis of their rewarding properties, potentially enabling the use of the procedure in consumer studies.